Upaya Meningkatkan Pemahaman Konsep Dengan Model Pembelajaran Inkuiri - Surya Safii; Lisa Ariyanti Pohan; Susylawati Sinambela (Departement of Mathematics Education, 2024)
This study used Classroom Action Research (CAR) aimed at improving the conceptual understanding of students in class X-3 at SMA Negeri 14 Medan on the topic of square roots and logarithms through the implementation of an inquiry-based learning model. Based on the research results and discussion, it can be concluded that the inquiry-based learning model is effective in enhancing the students' conceptual understanding. There was an improvement in students' conceptual understanding from Cycle 1 to Cycle 2, where the average class score increased from 69.87 with a classical mastery of 42.42% in Cycle 1 to an average score of 75.88 with a classical mastery of 75.76% in Cycle 2. This increase of 33.34% in classical mastery indicates significant improvement. Additionally, the learning process between the teacher and students in Cycle 2 was also better compared to Cycle 1.